2022
DOI: 10.1002/aenm.202201509
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Regulation of Oriented Crystallization and Interfacial Passivation Enables 19.1% Efficient Wide‐Bandgap Perovskite Solar Cells

Abstract: show promising applications in buildingintegrated photovoltaics and Internet of Things. [4] Despite their numerous studies, WBG PSCs still suffer from severe opencircuit voltage loss (V loss ) and instability. Extensive investigations indicate that the rigorous V loss is attributed to high-density defects and photoinduced phase segregation. [5] The polycrystalline perovskite films prepared by solution methods have numerous defects at grain boundaries, surface, and perovskite bulk, [6] which act as trapping si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…[24,37] Other research proposed the concept that the polymer as the template can modulate the nucleation and growth of perovskite film, but how the polymer modulate the crystallinity process of perovskite remains unclear. [33,36,39] Furthermore, among various additives, fluorinate additives incorporated into perovskite layer [42][43][44] or as the interlayer on top of perovskite [45,46] facilitate the formation of hydrogen-fluorine bonds with organic cations, which protects perovskite from moisture.…”
Section: Introductionmentioning
confidence: 99%
“…[24,37] Other research proposed the concept that the polymer as the template can modulate the nucleation and growth of perovskite film, but how the polymer modulate the crystallinity process of perovskite remains unclear. [33,36,39] Furthermore, among various additives, fluorinate additives incorporated into perovskite layer [42][43][44] or as the interlayer on top of perovskite [45,46] facilitate the formation of hydrogen-fluorine bonds with organic cations, which protects perovskite from moisture.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have also been reported in 2D/3D hybrid systems previously. [39] Recent studies have demonstrated that the strains in perovskite film played a vital role in governing the carrier dynamics. [42] Here, the effects of 2D perovskite addition on regulating the film strains were investigated by depthresolved grazing incident X-ray diffraction (GIXRD) technique with 2θ-sin 2 ψ method.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Yu et al . reported that 4-fluoro-phenylethylammonium iodide as a bifunction additive promoted perovskite crystals to grow along with the (100) orientation and comprehensively passivated WBG perovskites, achieving a V OC of 1.30 V in WBG PSCs [ 33 ]. Potassium halides have been introduced to WBG perovskites to passivate defects, suppress ion migrations [ 32 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%